1980
DOI: 10.1080/03014468000004071
|View full text |Cite
|
Sign up to set email alerts
|

Changes in plasma urate, creatinine, alkaline phosphatase and the 24 hour excretion of hydroxyproline during sexual maturation in adolescents

Abstract: The relative concentrations of plasma uric acid and creatinine, the alkaline phosphatase activities and the 24 hour urinary excretion of hydroxyproline together with sexual maturity ratings are reported in a population of normal British schoolchildren studied longitudinally over a three-year period. The children were all of European origin and their ages ranged from 7 to 17 years. Plasma urate rose sharply during puberty in the boys but not in the girls. Plasma creatinine rose in both sexes during maturation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…44, 45 As significant differences in uric acid levels between male and female adolescents were noted in this and previous studies, the association between uric acid level and elevated blood pressure was examined stratified by sex. 44-47 Males had a higher odds than females of having an elevated blood pressure with increasing uric acid level. It is likely that the lower uric acid levels observed in females in the cohort may be diluting the association with elevated blood pressure, as an interaction between uric acid and sex was not statistically significant.…”
Section: Discussionmentioning
confidence: 79%
“…44, 45 As significant differences in uric acid levels between male and female adolescents were noted in this and previous studies, the association between uric acid level and elevated blood pressure was examined stratified by sex. 44-47 Males had a higher odds than females of having an elevated blood pressure with increasing uric acid level. It is likely that the lower uric acid levels observed in females in the cohort may be diluting the association with elevated blood pressure, as an interaction between uric acid and sex was not statistically significant.…”
Section: Discussionmentioning
confidence: 79%
“…In the present study a clear sex difference was observed. Since serum uric acid is known to vary with sex (Munan, Kelly and Petitclerc 1976, (Mikkelsen et al 1965, Bengtsson andTibblin 1974), and sexual maturity (Round 1980), this suggests that these variables, along with height and weight, need to be considered in future studies of uric acid and blood pressure in adolescents.…”
Section: Serum Uric Acid and Blood Pressurementioning
confidence: 97%
“…This rise in uric acid occurred to the same extent in both black and white youths; however, the white youths reached their adult plateau at 15 while the black youths reached it at 16-17. Round (1980) examined the association of serum uric acid levels and the sexual maturity of boys and girls. She found increases in uric acid in males but not in females to be associated with increasing sexual maturity.…”
Section: Introductionmentioning
confidence: 99%
“…For a clinical description of these conditions, see Chapter 14. bTNAP is secreted by osteoblasts and promotes bone mineralisation. Circulating TNSAP is largely derived from liver and bone, and its levels in plasma during childhood reflect the growth rate [55] and are raised in the presence of rickets (see Chapter 8), in Juvenile Paget's Disease (#239000) and in fibrous dysplasia (see Chapter 14). Low TNSAP levels are seen in hypophosphatasia, which results from mutations in the TNAP gene.…”
Section: Alkaline Phosphatasementioning
confidence: 99%